If you would like to evaluate 6 * [5 * (3 - 9) - 1] + 2 / 7 * (8 - 2) + 4, you can calculate this using the following steps:
6 * [5 * (3 - 9) - 1] + 2 / 7 * (8 - 2) + 4 = 6 * [5 * (-6) - 1] + 2/7 * 6 + 4 = 6 * [- 30 - 1] + 12/7 + 4 = 6 * [- 31] + 12/7 + 4 = - 186 + 12/7 + 4 = - 182 + 12/7 = - 1274/7 + 12/7 = - 1262/7
The correct result would be - 1262/7.
Answer:
x just represents a number
Answer:
2(2-x)+12x=44
4-2x+12x=44
-4 -4
-2x +12x = 40
10x=40
/10 /10
x=4
Step-by-step explanation:
first you multiply the (2-x) by 2, you then subtract the 4 from both sides of the equation, you end up with -2x +12x = 40. Then subtract the 2x from the 12x and you end up with 10x. so now 10x=40. You then divide both sides by 10 and end up with x=10
sorry im not to good at explaining haha